Verification of hypocholesterolemic effect of fermented milk on human subjects with different cholesterol levels - Ashar, M N; Prajapati, J B (Folia microbiologica, 2000)
The possible hypocholesterolemic effect of acidophilus milk was evaluated on 27 human subjects having different levels of serum cholesterol, i.e. < 2.0 (group C1), 2.0-2.2 (C2), 2.2-2.5 (C3) and > 2.5 g/L (C4). The acidophilus milk was prepared by fermentation of low-fat milk with Lactobacillus acidophilus and was fed to each volunteer at the rate of 200 mL/d for 20 d. Blood samples from the volunteers were collected and analyzed for lipid profile twice prior to, during and after feeding, keeping a gap of 10 d between two collections. A significant decrease (p < 0.05) in average total cholesterol was found in the C2 and C3 groups, amounting to 21 and 12%, respectively. The average LDL cholesterol decreased in C2, C3 and C4 groups by 0.54, 0.26 and 0.46 g/L, respectively. In the C2 group, the LDL/HDL and total/HDL ratio was also reduced by 1.4 and 1.3, respectively. However, in the C1 group, the average total and LDL cholesterol level did not show any significant change but serum triacylglycerols and VLDL cholesterol showed a significant (p < 0.05) increase of 0.53 and 0.11 g/L, respectively. Regression analysis of the data revealed a square trend in most of the parameters over time period. Overall, the feeding had the best effect in the subjects with lipidemic status of borderline cholesterol level (2.0-2.2 g/L) group.
Keywords: Cholesterol, HDL; Lactobacillus acidophilus; Cholesterol; Triglycerides; hyperlipidemie; cholesterol; lipidy; Lipids; Animals; Milk; lidé; HDL-cholesterol; Hyperlipidemias; Humans; zvířata; triglyceridy; mléko